Rhetorical Strategy and Agenda Setting in Political Communication: The Discursive Power of the ‘Gerbang Baru Nusantara’ Slogan in the 2024 East Java Election - Rosi, Fitriyanti; Rahayu, Efria Tika (Generasi Sains Indonesia, 2025)
This study offers a comprehensive examination of the complexities surrounding digital piracy and copyright enforcement in the contemporary digital landscape, with a particular focus on the implications of the Digital Millennium Copyright Act (DMCA). Through a multi-method approach encompassing document analysis, semi-structured interviews, case studies, and illustrative examples, the study delves deep into legal frameworks, socio-cultural dynamics, and technological advancements shaping the digital copyright landscape. Findings reveal nuanced insights into the challenges and opportunities for addressing digital piracy while preserving innovation, creativity, and equitable access to digital content. Key recommendations for policymakers, legal practitioners, industry stakeholders, and researchers are provided to inform evidence-based interventions and future research endeavors in the field of digital copyright enforcement.